DIGITAL TRANSFORMATION OF THE REGIONS OF UKRAINE AS A PREREQUISITE FOR THE IMPLEMENTATION OF THE SMART CITY CONCEPT - KIZLYAR, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to researching the processes of digital transformation of the regions of Ukraine through the implementation of the "smart city" concept, which is one of the key aspects of the modern development of urban areas. In the context of global trends towards digitization and the introduction of innovations, the concept of a smart city is becoming an important part of the strategic planning of both large megacities and medium and small cities. This is due to the need to adapt cities to the rapidly changing socio-economic environment, which requires more effective solutions for managing resources, improving the quality of life of residents and increasing competitiveness in the international arena. The article examines the relevance of the transition to "smart cities" in light of the challenges facing modern Ukraine, including economic, environmental and social aspects. The main challenges that stand in the way of implementing the concept of a smart city in Ukrainian regions are analyzed. Such challenges include an insufficient level of digital infrastructure, limited financial resources, a low level of digital literacy of the population, an incomplete legal framework, and an insufficient level of interaction between the public and private sectors. The article analyzes the current state of digital infrastructure in different regions of Ukraine, in particular, the level of access to broadband Internet and the implementation of intelligent transport management systems. In addition, a comparison of the implementation of smart city projects in Ukrainian cities with similar initiatives in Europe is presented, which emphasizes the need to accelerate digital transformation in the face of global competition.